Language and action in cognitive neuroscience - Coello, Yann.; Bartolo, Angela (London ; New York : Psychology Press, 2013)
"This book collates the most up to date evidence from behavioural, brain imagery and stroke-patient studies, to discuss the ways in which cognitive and neural processes are responsible for language processing. Divided into six sections, the edited volume presents arguments from evolutionist, developmental, behavioural and neurobiological perspectives, all of which point to a strong relationship between action and language. It provides a scientific basis for a new theoretical approach to language evolution, acquisition and use in humans, whilst at the same time assessing current debates on motor system's contribution to the emergence of language acquisition, perception and production. The chapters have been written by internationally acknowledged researchers from a variety of disciplines, and as such this book will be of great interest to academics, students and professionals in the areas of cognitive psychology, neuropsychology, neuroscience, psycholinguistics and philosophy"--
section 1. Language and action : past, present and future -- section 2. The motor origin of language -- section 3. Action in language processing -- section 4. Action in language acquisition -- section 5. Action in spatial language and numbers -- section 6. Language and action within the brain -- section 7. Language and action in cognitive neuroscience : a final note.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Neurolinguistics; Speech -- Physiological aspects; Brain -- Localization of functions; Cognition; Electronic books